2002
DOI: 10.1006/nimg.2002.1175
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Regularization of Linear Inverse Solutions of the EEG Source Localization Problem

Abstract: Distributed linear solutions of the EEG source localization problem are used routinely. Here we describe an approach based on the weighted minimum norm method that imposes constraints using anatomical and physiological information derived from other imaging modalities to regularize the solution. In this approach the hyperparameters controlling the degree of regularization are estimated using restricted maximum likelihood (ReML). EEG data are always contaminated by noise, e.g., exogenous noise and background br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(104 citation statements)
references
References 40 publications
1
103
0
Order By: Relevance
“…PEB requires a hierarchical observation model where the parameters and hyperparameters at any particular level can be treated as priors on the level below. In the context of the EEG inverse problem, this modelling strategy has already been employed successfully in Phillips et al, 2002) for constraining the spatial deployment of distributed sources. These models parameterize the prior covariance of dipole dynamics with a linear mixture of a priori covariance components.…”
Section: Relation To Existing Approachesmentioning
confidence: 99%
“…PEB requires a hierarchical observation model where the parameters and hyperparameters at any particular level can be treated as priors on the level below. In the context of the EEG inverse problem, this modelling strategy has already been employed successfully in Phillips et al, 2002) for constraining the spatial deployment of distributed sources. These models parameterize the prior covariance of dipole dynamics with a linear mixture of a priori covariance components.…”
Section: Relation To Existing Approachesmentioning
confidence: 99%
“…The major problem here is the introduction of multiple constraints and their appropriate weighting, while accounting for observation noise (Gonzalez Andino et al, 2001). In Phillips et al (2002b), we introduced a simple bRestricted Maximum LikelihoodQ (ReML) procedure to estimate a single hyperparameter, i.e., balance between fitting the data and conforming to the priors. Here we reformulate the WMN solution in terms of a hierarchical linear model.…”
Section: Introductionmentioning
confidence: 99%
“…Inverse problems arising in the analysis of data obtained by Electrical Impedance Tomography (EIT) and Single Photon Emission Tomography (SPET) have been formulated as state estimation problems (Karjalainen et al 1997;Kaipio et al 1999;Vauhkonen et al 2001) , and the use of Kalman filtering and Kalman smoothing has been suggested for the purpose of obtaining estimates of the state. Phillips et al (2002) have suggested to introduce a temporal constraint into the EEG/MEG inverse problem by employing a time window and Gaussian kernels.…”
Section: Introductionmentioning
confidence: 99%